Left-Handedness and Male-Male Competition: Insights from Fighting and Hormonal Data - Charlotte Faurie; Violaine Llaurens; Alexandra Alvergne; Marcel Goldberg; Marie Zins; Michel Raymond (Evolutionary Psychology, 2011)
Male-male competition can shape some behavioral or morphological traits of males. Here we investigate if this competition could play a role in the persistence of the polymorphism of handedness in human populations. A negative frequency-dependent selection mechanism has been hypothesized, based on the fact that left-handed men may benefit from a “surprise” advantage during fighting interactions because they are rare in human populations. This advantage may thereby enhance the probability of survival of left-handed men and/or their reproductive success through an increase in social status. In this study, we first explored the association between hand preference and lifetime fighting behavior in a population of 1,161 French men. No effect of hand preference on the probability of fighting was detected, suggesting that the innate propensity to fight does not differ between left- and right-handers. However, among men who had been involved in at least one fight during their lifetime, left-handers reported significantly more fights than right-handers. To explore the biological basis of this behavior, we also investigated the testosterone concentration in saliva samples from 64 French university students. Consistent with frequencies of fights, we found a significantly higher average testosterone concentration in left-handers than in right-handers. We suggest that these behavioral and hormonal differences may be acquired throughout life due to previous experiences in a social context and may favor the persistence of left-handers in humans.